2020
DOI: 10.20944/preprints202004.0195.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and the Digital Transformation of Education: What We Are Learning in South Africa

Abstract: The study sought to gauge the impact of COVID-19 pandemic in unleashing digital transformation in the education sector in South Africa. In order to gauge the impact, the study tracked the rate at which the 4IR tools were used by various institutions during the COVID-19 lockdown. Data were obtained from secondary sources, mainly newspaper articles, magazines and peer-reviewed journals. The findings are that, in South Africa, during the lockdown, a variety of 4IR tools were unleashed from primary education to hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 2 publications
0
23
0
4
Order By: Relevance
“…The ministry of communication and digital technologies led the initiative. Through the minister, an announcement was made that the departments of communications and digital technologies and basic education had joined forces, to ensure virtual learning is a reality during the nation-wide lockdown [24,25]. This move was necessitated by both the closure of schools during the lockdown and the desire to mitigate the impact of COVID-19 on the education sector.…”
Section: The Impact Of Covid-19 On Digital Transformation Towards the 4irmentioning
confidence: 99%
See 2 more Smart Citations
“…The ministry of communication and digital technologies led the initiative. Through the minister, an announcement was made that the departments of communications and digital technologies and basic education had joined forces, to ensure virtual learning is a reality during the nation-wide lockdown [24,25]. This move was necessitated by both the closure of schools during the lockdown and the desire to mitigate the impact of COVID-19 on the education sector.…”
Section: The Impact Of Covid-19 On Digital Transformation Towards the 4irmentioning
confidence: 99%
“…This move was necessitated by both the closure of schools during the lockdown and the desire to mitigate the impact of COVID-19 on the education sector. The other reason is that the country was not prepared for the disruption, and as a result bringing in virtual classes was a way to find possible ways that technology could help address the disruption induced by COVID-19 [24,25].…”
Section: The Impact Of Covid-19 On Digital Transformation Towards the 4irmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, industry 4.0 is initiating new economic form in many sectors, the sharing economy (Mhlanga, 2020a, Mhlanga and Moloi, 2020b, Kravchenko and Kyzymenko, 2019. Services such as shared basketballs and toys; transport this shows how revolutionary the shared economy will become in the industry 4.0 (Mhlanga and Moloi, 2020a).…”
Section: 1the Difference Of the Industry 40/4ir To Other Revolutionsmentioning
confidence: 99%
“…According to a study "COVID-19 and the Digital Transformation of Education: What We Are Learning in South Africa", Mhlanga and Moloi (2020a) found out that despite the existence of social distancing restriction necessitated by COVID-19, technology helped many people to be able to have access to classes through online education. The study also found out that technology can increase access to education especially if education move from face to face type of education to online education where space is not a limiting factor (Bennington-Castro, 2017).…”
Section: 3the Impact Of Ai In Educationmentioning
confidence: 99%